Penilaian Kinerja APBDES Desa Purwodadi Dengan Menggunakan Analisis Rasio Keuangan - Arina Bunganingtyas,; Erisma Adi Natalian,; Herlina Manurung, (Manajemen Kreatif Jurnal, 2023)
The village is a unit of legal society which has territorial boundaries and regulates its own government affairs. The village government, one of the element of the village government, has full authority to carry out planned village activity programs. The implementation of village authority to carry out village activity programs funded by the Village Revenue and Expenditure Budget (APBDes) where village revenue comes from various sources. The research object used is the realization report on the implementation of the village revenue and expenditure budget of the Purwodadi village government for the 2020 and 2021 fiscal years. The type of data used is unit count. The data collection technique used is the document study technique and the research method used is descriptive method, data analysis using the independence ratio, compatibility ratio, growth ratio, efficiency ratio, and effectiveness ratio.